Sex Differences in Health-related Quality of Life in Patients with Keratinocyte Carcinomas - Francesca Sampogna; Andrea Paradisi; Maria Luisa Iemboli; Luca Fania; Francesco Ricci; Monica Napolitano; Damiano Abeni (Medical Journals Sweden, 2021)
The difference between men and women in the impact of keratinocyte carcinomas on quality of life has not been widely studied. This study of 364 patients with keratinocyte carcinoma, measured quality of life using the self-administered 12-item Short Form Health Survey (SF-12) and Skindex-29. Results for both the physical and the mental components of SF-12 were worse in women than in men. For the mental component, women had significantly lower scores compared with men in almost all subgroups, based on demographic and clinical variables. The Skindex-29 emotions mean score was worse in women than in men. Women reported significantly higher level of worry that the disease could get worse and of developing scars, and more depression. On the other hand, men reported lower quality of sleep. The impact of keratinocyte carcinomas on quality of life is generally higher in women than in men. Such data may be important for tailored management of the disease in different categories of patients.